Taxonomic novelties in Erysimum for the Flora of Iran: E. polatschekii, a new alpine endemic, and E. scabrum, a new record - Moazzeni, Hamid; Assadi, Mostafa; Zare, Golshan; Mirtadzadini, Mansour; Al-Shehbaz, Ihsan A. (Phytotaxa, 2016)
During the work on herbarium material to prepare a taxonomic revision of Erysimum for the Flora of Iran, we found two interesting species not previously known for the country. Erysimum polatschekii is described as new from the alpine zone of Kerman Province (S Iran). It is closely related to the allopatric E. purpureum and E. pseudopurpureum, from which it differs by having bicolored flowers, clearly 2-lobed stigma, winged seeds, and different fruit indumentum.  Erysimum scabrum, which grows in Lebanon, Syria, and Turkey, is recorded herein as new to the flora of Iran. Detailed descriptions, distribution maps, and illustrations for both species are provided.